Impacts of Amazon Fire Aerosols on the Subseasonal Circulations of the Mid-High Latitudes - Zhou, Yu; Yan, Huiping; Luo, Jing-Jia (Frontiers in Earth Science, 2021)
The strong radiative effects of fire aerosols have been well accepted in climate community. However, there have been few studies on the aerosol effects at monthly to subseasonal range. We used the National Centers for Environmental Prediction (NCEP) reanalysis datasets and Community Atmosphere Model Version 5 (CAM5) to explore the impacts of Amazon fire aerosols on the subseasonal climate. With the reanalysis datasets, we found that most of the abnormal high emissions concurred with La Nina events. And the composite analysis of the abnormal high emissions showed that there is a La Niña-like pattern sea surface temperature anomalies (SSTA), precipitation, and circulation anomalies. To isolate the aerosol impacts from the SSTA, we removed the linear regressions of nino3.4 SST index, and found that significant anomalies in pressure field still persisted in the midlatitude. Five waves can be found in the mid-high latitudes of both Hemisphere induced by Amazon fire aerosols. Through prescribing climatology SST and La Niña-like SSTA in CAM5 simulations, we found only the later could reproduce the aerosols impacts on circulation in the mid-high latitudes, i.e. the 5-wave anomalies, although with biased locations. This indicates that the Amazon wildfire aerosol impacts are highly coupled with the La Nina-like SSTA. This study emphasizes that Amazon fire aerosols indeed result in significant circulation anomalies in the mid-high latitudes and including the fire aerosols may improve the model forecasting skills at monthly to subseasonal scales.